Prevention of stillbirth. (7th July 2015) - Smith, Gordon CS
<x xml:space="preserve">Abstract</x> Key content Most of the variability in stillbirth risk is not due to maternal risk factors, therefore modifying maternal risk factors or screening women using maternal risk factors to assess risk has limited potential impact. The primary intervention that prevents stillbirth is delivery. The overall risk of perinatal death is lowest at 39 weeks of gestation, and induction of labour at term does not increase a woman's risk of emergency caesarean section. The most promising approach to screening low risk women for stillbirth risk may be to improve identification of small‐for‐gestational‐age infants; however, there is an absence of high quality evidence around the optimal approach for achieving this goal. Learning objectives To understand the relationship between maternal risk factors, obstetric complications and fetal size in relation to stillbirth risk. To understand the approach to fetal assessment and elective delivery as methods to prevent stillbirth. Ethical issues Screening for stillbirth risk has the potential to do good by preventing deaths. However, if programmes of screening and intervention are developed, many more women may be harmed due to high false positive rates.